Implementation of two-function fish pellet machine for empowerment of fish cultivator group Gelondoro Sidoarjo - Izza Anshory; A’rasy Fahruddin; Lukman Hudi (Universitas Muhammadiyah Magelang, 2022)
In the post-Covid-19 pandemic, the Gelondoro fish cultivator group, Jabon Sidoarjo District, had difficulties meeting fish feed pellets' needs. This difficulty is caused by the increase in the price of fish feed pellets; both groups of fish cultivators have very little knowledge of making fish feed pellets. The purpose of this community service activity is to empower the Gelondoro farmer group to produce fish feed pellets independently to meet their needs without depending on factory feed. The method used in this community service activity is to provide socialization regarding the formulation of fish feed pellets with high protein. The second is to provide a fish feed pellet machine with two functions: mixing and printing in one tool. The third demonstrates the manufacture of fish feed pellets. The result of this community service activity is that Gelondoro fish cultivators have known the formulation of a mixture of making fish pellets as well as practicing how to make fish feed pellets using a two-function fish pellet printing machine.